Application of Biofertilizer Consortium of Strain Bacillus sp with Different Concentrations and Aplication Methods on Growth of Nutmeg Seeds (Myristica fragrans Houtt) - A. Marthin Kalay; Henry Kesaulya; Abraham Talahaturuson; Herman Rehatta; Reginawanti Hindersah (Faculty of Agriculture, Pattimura University, 2020)
The growth of nutmeg seeds requires adequate nutrition by mechanism of bacteria activity associated with roots and leaves. The aim of study was to determine the effect of application of bacillus strain consortium biofertilizer on nutmeg seedlings. The experiment was arranged by using completely randomized design with 0% of PBH as control, and 0.15% and 0,30% of PBH concentration by spraying to leaves and by pouring in the soil around the stem, respectivelly. The results showed that the application of 0.15% and 0.30% of PBH concentration has significant effect in plant height, shoot dry weight, dry weight root and plant dry weight, but not at the number of root, root length, stem diameter, and the ratio of shoot and root dry weight of nutmeg seedlings after four month planting in the polybag. The concentration of PBH 0.30% has a greater influence on the nutmeg seed growth, and can be a solution to increasee seed growth.